Eliza Fenwick early modern feminist - Paul, Lissa 1953- (University of Delaware Press, 2019)
This captivating biography traces the life of Eliza Fenwick, an extraordinary woman who paved her own unique path throughout the late eighteenth and nineteenth centuries as she made her way from country to country as writer, teacher, and school owner.0Lissa Paul brings to light Fenwick's letters for the first time to reveal the relationships she developed with many key figures of her era, and to tell Fenwick's story as depicted by the woman herself. Fenwick began as a writer in the radical London of the 1790s, a member of Mary Wollstonecraft's circle, and when her marriage crumbled, she became a prolific author of children's literature to support her family. Eventually Fenwick moved to Barbados, becoming the owner of a school while confronting the reality of slavery in the British colonies. She would go on to establish schools in numerous cities in the United States and Canada, all the while taking care of her daughter and grandchildren and maintaining her friendships through letters that, as presented here, tell the story of her life
Keywords: Fenwick, Eliza -- 1766-1840; Fenwick, E. / (Eliza); Women authors, English / 19th century / Biography; BIOGRAPHY & AUTOBIOGRAPHY / General; Women authors, English; Fenwick, Eliza; 1800-1899; Biographies; Biografie